MARKETING MODEL OF DEVELOPING THE POTENTIONAL OF SMEs BASED ON SWOT ANALYSIS - Dewi Andriany (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to explore the strengths,weakness,opportunities and threats for Small and Medium Enterprises(SMEs)actors in conducting their business,in addition to theefforts that have been maede parties in developing SMEs.Using a focus group discussion with SMEs actors relevant agencies and banks does the dta collection.